Hidden features of the emerging sexuality of older adults: a phenomenological study - Marcos Augusto Moraes Arcoverde; Liliana Maria Labrinici (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2008)
Sexuality is a part of the human dimension that comes along with the living body throughout their existential trajectory, the reason because the individual do not west it in time, than it can be experienced in early age. From that concept it was developed a phenomenological study of nature which aimed to understand how the elderly understand and live their sexuality, being held in the period of January to July 2006, with ten senior citizens between 61 and 83 years old, who live in city of Curitiba (Brasil). The objective was to perceive as the aged one understands and lives its sexuality. The data of the study were obtained using a semi-structured interview recorded by digital media. The process of the analysis of speeches followed the moments of the phenomenological description trajectory: description, reduction and phenomenological understanding. From this study three themes emerged. This article describes only the theme ";;;;Hidden Faces and the emerging sexuality";;;;. We note that this research allowed us to realize how the elderly people perceive and experience their sexuality, and also it provided an opportunity to understand the importance of companionship, socialization and recreational activities as a vehicle of expression for sexuality. It also describes the phenomenon that points to the expansion of the approach of sexuality in the elderly, since it has proven to transcend the biological aspects intensely broadcasted when this topic is discussed.